The complete mitochondrial genome of Echinolaelaps fukienensis provide insights into phylogeny and rearrangement in the superfamily Dermanyssoidea. - Gangxian He; Wei Li; Bili Yuan; Wenge Dong (PLoS ONE, 2023)
Background Echinolaelaps fukienensis is the dominant mite species parasitic on the body surface of the genus Niviventer. The mitochondrial genome (mitogenome) has its own independent genetic material and genetic system, and is now widely used in population genetics, genealogical biogeography, phylogeny and molecular evolution studies. Species diversity of the superfamily Dermanyssoidea is very rich, but its mitogenomes AT content is high, and it is difficult to amplify the complete mitogenome by routine PCR. To date, we have only obtained the mitogenomes of 6 species, scarcity on sequence data has greatly impeded the studies in the superfamily Dermanyssoidea. Methods Echinolaelaps fukienensis were collected in 2019 from the body surface of Niviventer confucianus (Rodentia, Muridae) in Yunnan Province. The E. fukienensis mitogenome was determined and analyzed for the first time using the Illumina Novoseq 6000 platform. Phylogenetic analyses of the superfamily Dermanyssoidea were conducted based on the entire mitogenome sequences. Results The E. fukienensis mitogenome was 14,402 bp, which is known the smallest genome of the superfamily Dermanyssoidea, encoding a total of 37 genes, including 13 PCGs, 22 tRNAs, 2 rRNAs and 1 control region. Most protein-coding genes use ATN as the start codon and TAN as the stop codon. AT and GC skew of atp8 genes in E. fukienensis were both 0. The average length of 22 tRNA genes of E. fukienensis was 64 bp, and secondary structures of tRNAs showed base mismatches and missing D-arms in many places. Compared with gene arrangement pattern of the hypothetical ancestor of arthropods, the E. fukienensis mitogenome shows a novel arrangement pattern. Phylogenetic tree supported the monophyly of the superfamily Dermanyssoidea. Echinolaelaps fukienensis being the least genetic distant (0.2762) and most closely related to Varroa destructor. Conclusions This study analyzed comprehensive the structure and evolution of the E. fukienensis mitogenome for the first time, enriches molecular data of the genus Echinolaelaps, which will contribute to further understand phylogeny and rearrangement patterns of the superfamily Dermanyssoidea.